Determination of 2V in plagioclase by the analytical method using φ values multiple of 45° - Abrahão, Ibrahim Octavio (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1974)
The application of Chomard's method to plagioclases was studied by means of extinction operations in which φ is a multiple of 45°. A total of 240 extinction operations were performed in seven twinned grains, totaling 13 individuals. Twelve extinction operations (φ, θ, ψ) were done for each individual as follows: θ = 15°, θ = 30° and θ = 45°, φ = 45°, φ = 135°, φ = 225°, φ = 315°. A computer program was used to determine 2V and the direction angles of the optic axes. These results were compared to those obtained by the following methods: twins, direct measurement and maximums extinction angle. Stereograms obtained by the analytical and conventional methods were also compared. The main conclusion drawn was that the computer programmed analytical method is as efficient as the otheres when θ = 30° and the 2V position is considered to be the average of the 4 possible analytical solutions where the value of φ is a multiple of 45°.